LEGISLATIVE GAPS OF GEORGIAN CIVIL CODE WITH REGARD TO THE INSTITUTIONS OF THE CONTRACT COMPLETION (Law and world, 2023)
The article“Legislative gaps of Georgian Civil Code with regard to the institutions of the contract completion” deals with the most important institutions of civil law, such as: withdrawal from the contract and termination of the contract, legislative gaps of the Georgian Civil Code in respect of them and judicial practice. Abovementioned issues were considered in accordance with the Georgian civil law and it is compared with the German Civil Code. The theme is divided into the following parts: introduction, institutions’ comparative analyzes of the contract termination and the dissolution of the contract, legislative practice and conclusions. The article also deals with the gaps that are characterized in Georgia’s Civil Code and recommendations for legislators they are required to comply with, and also recommendations to eliminate even terminological gaps existing in Georgia’s Civil Code. The article was targeted at junior lawyers, as well as law interested persons. The work will help them to better understand the essence of the instrument of the completion of the contract and to use it for its intended purpose.